APPLICATION OF LEARNING MANAGEMENT SYSTEMS (LMS) IN DISTANCE EDUCATION: A LITERATURE REVIEW - Novianty Djafri; Suhana Sarkawi; Rusiadi (Review of International Journal Education and School Leadership, 2025)
The application of Learning Management Systems (LMS) in distance education plays an important role in supporting teaching and learning in the digital era. This article reviews various literatures to evaluate the effectiveness, benefits, and challenges faced in using LMS. The review shows that LMS can improve the flexibility and quality of learning by providing various digital features such as material storage, evaluation system, and online communication. However, LMS implementation is also faced with a number of obstacles such as limited internet access, lack of technological literacy, and cost factors. In conclusion, the success of LMS implementation is highly dependent on educational policy support, user training, and adequate infrastructure readiness. With the right attention and management, LMS has great potential to optimise distance education and promote inclusivity in the education system.